2018
DOI: 10.3390/catal8100419
|View full text |Cite
|
Sign up to set email alerts
|

Novel Bifunctional Mesoporous Catalysts Based on Preyssler Heteropolyacids for Green Pyrrole Derivative Synthesis

Abstract: In this paper, we report the synthesis of Preyssler heteropolyacids supported on mesoporous alumina in order to obtain materials with acid–base properties. A series of pyrrole derivatives were synthesized using a suitable procedure under solvent-free conditions. Using the alumina-supported material, more complex pyrrole derivatives can be obtained through a tandem one-pot process that involves the formation of 2-amino-3-cyano 4-H-chromenes by a multicomponent reaction and their subsequent conversion to pyrrole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…The loading of HPAs on suitable solid supports can overcome the issues of low specific surface and high solubility of HPAs; furthermore, supports can provide additional reaction sites. [87]. A series of polyfunctionalized 3-pyrrolin-2-ones can be obtained with yields of 81%-93% under mild conditions with a short reaction time.…”
Section: Hpas Supported On Suitable Solid Supportsmentioning
confidence: 99%
“…The loading of HPAs on suitable solid supports can overcome the issues of low specific surface and high solubility of HPAs; furthermore, supports can provide additional reaction sites. [87]. A series of polyfunctionalized 3-pyrrolin-2-ones can be obtained with yields of 81%-93% under mild conditions with a short reaction time.…”
Section: Hpas Supported On Suitable Solid Supportsmentioning
confidence: 99%
“…Our research group reported a suitable method for pyrrole synthesis using the Paal-Knorr methodology [67] ) with the aim of preparing materials with acid-base properties. The materials were synthesized by the water impregnation method, and the characterization determined that the intact structure was preserved.…”
Section: Pyrrolesmentioning
confidence: 99%
“…Heterogeneous catalysts containing Bronsted acid sites or Lewis acids sites are good candidates, and typical examples included layered zirconium sulfophenyl phosphonate, sulfated zirconia, zeolites, montmorillonite clay, graphene oxide, tungstate sulfuric acid (TSA), molybdate sulfuric acid (MSA), and so on. Another type of heterogeneous catalysts was Bronsted acid or Lewis acids immobilized on solid supports, such as supported sulfuric acid, Preyssler heteropolyacids, diethylene­triaminepenta­acetic acid, polyethylene glycol 400 coated with sulfonic acid groups, sulfamic acid, antimony­(III) chloride (SbCl 3 ), and gallium trichloride supported (GaCl 3 ) . Compared to homogeneous acids, those solid/supported acids were easily reused, and in addition, their stability, hygroscopic properties, and ease of handling were significantly enhanced, which were important in industry usage …”
Section: Production Of Organonitrogen Chemicals From Oxygen-containin...mentioning
confidence: 99%